Urbanization, Biodiversity and Ecosystem Services : A Global Assessment. - Elmqvist, Thomas; Fragkias, Michail; Goodness, Julie; Güneralp, Burak; Marcotullio, Peter J.; McDonald, Robert I.; Parnell, Susan; Schewenius, Maria; Sendstad, Marte; Seto, Karen C. (Dordrecht : Springer Netherlands, 2013)
This book offers a global analysis of how urbanization and urban growth impact biodiversity and ecosystem dynamics in terrestrial, freshwater, and marine systems. It develops a new theoretical framework for urban sustainability and resilience.
17.5.1 Informal Institutions and Management.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books